2000
DOI: 10.1002/1521-3757(20001117)112:22<4256::aid-ange4256>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Oxidosqualene Cyclase Residues that Promote Formation of Cycloartenol, Lanosterol, and Parkeol

Abstract: We are grateful to Bridget M. Joubert for advice regarding mutagenesis. We thank Elizabeth A. Hart for an authentic parkeol standard, and for chromatographic and spectroscopic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…It has been shown that wild-type Arabidopsis CAS, expressed in a yeast mutant, is able to produce 1% parkeol, but not lanosterol (<0.1%) [28]. Moreover, the possibility to generate an enzyme that makes parkeol as its major product from either CAS [28,59,60] or lanosterol synthase [61,62] has been reported. As an example, the work by Segura et al [60] has emphasized the critical role played by His477, which is strictly conserved in all CAS.…”
Section: Origin Of the Structural Diversity Of Triterpenoids In Olivementioning
confidence: 99%
“…It has been shown that wild-type Arabidopsis CAS, expressed in a yeast mutant, is able to produce 1% parkeol, but not lanosterol (<0.1%) [28]. Moreover, the possibility to generate an enzyme that makes parkeol as its major product from either CAS [28,59,60] or lanosterol synthase [61,62] has been reported. As an example, the work by Segura et al [60] has emphasized the critical role played by His477, which is strictly conserved in all CAS.…”
Section: Origin Of the Structural Diversity Of Triterpenoids In Olivementioning
confidence: 99%
“…OSC have been purified and cloned from different species: Candida albicans, Saccharomyces cerevisiae, and Schizosaccharomyces pombe among the fungi; higher plants; the rat; the pig; and human (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). SHC from Alicyclobacillus acidocaldarius has recently been overexpressed in Escherichia coli, purified, and crystallized (18)(19)(20).…”
mentioning
confidence: 99%
“…All other eukaryotes that have been examined in this regard (at least members of the higher plants, green and red algae, amoebozoa, diatoms, euglenids and heterolobosea) make cycloartenol as their protosterol. Site-directed mutagenesis experiments, notably those of Matsuda and co-workers (Meyer et al 2000Joubert et al 2001;Segura et al 2002;Lodeiro et al 2004) have indicated the key residues that control the product profile of OSCs, including T381, C449 and V453. From analysis of the crystal structure, each appears to affect the position of the catalytic base dyad H232-Y503.…”
Section: Resultsmentioning
confidence: 99%